Liver abnormalities in Wistar rats exposed to oral intake of polyvinyl chloride microplastics - Sincihu, Yudhiakuari; Keman, Soedjajadi; Mohd Elias, Saliza; Mastan, Johanes Adiatna; Morina, Shella (AnKa Publisher, 2022)
Microplastics is a food contaminant. Smaller microplastics can penetrate into the blood circulation system and bioaccumulate in the liver. It can induce oxidative stress in hepatocytes, resulting in damage. The aim of this experimental study was to compare the levels of functional biomarkers, anatomical, and histopathological features of the liver due to oral microplastics exposure. Fourteen white rats were used and equally divided into two groups. The experimental group (E) was given 0,5mg polyvinyl chloridemicroplastics dissolved in 1cc of distillated water per day, while the control group (C) was only given distillated water. Both groups were given orally for 28 days using a probe. Therewasno difference in blood level of serum glutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase, lactate dehydrogenase, tryglicerides, and total cholesterol between both groups. The anatomical features indicated a normal condition. Although it was not significant, experimental group’s liver weight (9.6±1,6grams) tended to be heavier compared to control group (8.7±1,4grams). The histopathological hallmarks of hepatocellular injury were more noticeable in experimental group, either a reversible process such as hepatocytes degeneration (C=119,5±34,6; E=186,7±11,5) or cell death (C=13,7±5,1; E=38,5±12,7). Statistical test showed very strong significance (p <0,01). Lobular inflammation and Kupffer cells were also more prominent. Oral intake of polyvinyl chloridemicroplastics in white rats causes hepatocellular injury, specifically hepatocyte degeneration. However, the dose of microplastics used was not sufficient to alter gross anatomy and biomarkers of liver function in blood.